Extraction and Some Functional Properties of Protein Extract from Rice Bran - Chockchai Theerakulkait; Siree Chaiseri; Siriwat Mongkolkanchanasiri (Agriculture and Natural Resources, 2006)
Rice bran protein extract (RBPE) was prepared from laboratory defatted rice bran (milled and sieved through 50 mesh screen) by alkali extraction. The extracting conditions that provided the maximum protein extractability were: extraction rice bran to water at ratio of 1:4 (w/v) at pH 9.5, agitating speed of 500 rpm for 45 min. The protein extractability was 44.4%of total protein in rice bran used for extraction. Protein solubility, emulsifying activity and emulsion stability index of RBPE were determined. The results showed that protein solubility, emulsifying activity and emulsion stability index of RBPE were the highest at pH 9 compared at other pHs (p≤0.05) with the values of 66.74%, 0.167 (A 500nm) and 43.15 min, respectively, while the lowest at pH 4 (p≤0.05) with the values of 10.75%, 0.063 (A 500nm) and 18.58 min, respectively.